Strategi Perpustakaan Universitas Widyatama dan Institut Teknologi Nasional dalam Memenuhi Kebutuhan Informasi - Keysha Husna Muchtarom; Evi Nursanti Rukmana (Media Pustakawan, 2024)
Widyatama University Library and National Institute of Technology Library are college libraries that manage collections and all information sources in higher education. This study aims to determine the strategy of college libraries in providing information sources through cooperation between Widyatama University Library and the National Institute of Technology Library. The research method is a qualitative approach with case study research, while the data collection techniques are observation, interview, document study, and literature study. The research participants involved in this study were the Head of Widyatama University Library and the librarians of the National Institute of Technology based on purposive sampling. The result of this study is a cooperation that has been carried out by Widyatama University Library and the National Institute of Technology Library, namely providing information sources in digital and printed form. Digital collection information sources are in the form of e-journals, learning videos, and e-books, while print collections are books, magazines, journals, and other learning materials in print. The conclusion of this research is that the cooperation carried out by both parties uses four strategies for providing information sources and provides eight positive impacts so that the two libraries extend their cooperation.